Obstacles Faced by The Curator, As Well As The Efforts Made by The Curator In Conducting Actio Pauliana Against Bankruptcy Assets - Sianipar, Mangatur Ruhut Banuara; Sahputra, Rilawadi; Sitompul, Ariman (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2024)
The formulation of the problem in this writing is how the rules of law governing the implementation of Actio Pauliana against bankruptcy assets, what factors are obstacles, as well as the efforts made by the curator in conducting Actio Pauliana against bankruptcy assets (based on Case Study decision Number: 1/Pdt.Sus-Actio Pauliana/2022 / Fr.Commerce. Mdn Jo. Number 32/Rev.Sus PKPU/2021 / Fr. Commerce.Mdn). In addition, how is the role of the curator in conducting Actio Pauliana against bankruptcy assets (based on a case study of decision Number: 1/Pdt.Sus-Actio Pauliana/2022 / Fr. Commerce.Mdn Jo. Number 32/Rev.Sus PKPU/2021 / Fr. Commerce.Mdn). The type of research that will be used in the writing of the thesis is empirical juridical research. The results of the study of factors that become obstacles, in conducting Actio Pauliana against bankruptcy assets based on decision Number: 1 / Pdt.Sus-Actio Pauliana/2022 / Fr. Commerce.Mdn Jo. No. 32 / Pdt.Sus Pkpu/2021 / Fr. Commerce.Mdn: 1. Juridical Aspect, 2. Non-Juridical Aspects: The Role Of The Curator In Conducting Actio Pauliana Against Bankruptcy Assets Based On Decision Number: 1 / Pdt.Sus-Actio Pauliana/ 2022 / Fr.Commerce. Mdn Jo. Number 32/Rev.Sus Pkpu/2021 / Fr.Commerce.Mdn: in doing Actio Pauliana, the curator must be able to prove that the legal action that has been done by the insolvent debtor/party that is closely related to the insolvent debtor is something that comes from the insolvent debtor and can harm or reduce the value of the insolvent boedel.